О связанной системе абстракных дифференциальных уравнений типа уравнений термоупругости - Герштейн, Л.М. (Український математичний журнал, 1993)
The study of a model system of differential equations arising from the dynamical problems of thermo elasticity is continued. The case of shifts of the general type is investigated. We employ the “commutant method” based on the properties of the operator ∆(A,B)=AB-BA.